Measurements of absolute, SI-traceable lunar irradiance with the airborne lunar spectral irradiance (air-LUSI) instrument. (1st June 2022) - Woodward, J T; Turpie, K R; Stone, T C; Gadsden, S A; Newton, A; Maxwell, S E; Grantham, S E; Larason, T C; Brown, S W
Abstract: The airborne lunar spectral irradiance (air-LUSI) instrument is designed to make low uncertainty measurements of the lunar spectral irradiance from an ER-2 aircraft from altitudes above 95% of the atmosphere. Measurements cover the visible and near infrared spectral region (350 nm to 1050 nm) and are traceable to the international system of units. Five demonstration flights were conducted in November 2019 at NASA's Armstrong Flight Research Center. During that campaign, air-LUSI measured the spectral irradiance at lunar phase angles ranging from 10° to 60°. This work provides an overview of the air-LUSI instrument, the lunar irradiance measurements made during demonstration flights, a description of our calibration approach, and summary of the uncertainty budget. Based on the flight results and laboratory measurements, we estimate the instrument is capable of measuring lunar irradiance, propagated to the top-of-the atmosphere, with combined standard uncertainty of 1% ( k = 1) or less over the spectral region from 450 nm to 980 nm. An examination of the uncertainty budget leads to a path forward toward potentially achieving uncertainties of 0.6% in lunar irradiance over much of the spectral range for future flights.